2019
DOI: 10.1111/ejn.14342
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of kinetic and kinematic movement parameters in the sensorimotor cortex: A Brain‐Computer Interface perspective

Abstract: For severely paralyzed people, Brain-Computer Interfaces (BCIs) can potentially replace lost motor output and provide a brain-based control signal for augmentative and alternative communication devices or neuroprosthetics. Many BCIs focus on neuronal signals acquired from the hand area of the sensorimotor cortex, employing changes in the patterns of neuronal firing or spectral power associated with one or more types of hand movement. Hand and finger movement can be described by two groups of movement features,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 161 publications
(240 reference statements)
5
20
0
Order By: Relevance
“…However, the presence of tonic elements agrees with intracortical studies (Smith et al, 1975;Wannier et al, 1991), which demonstrated both tonic and dynamic neural responses to executed forces; and fMRI studies (Branco et al, 2019), which demonstrated a monotonic relationship between the BOLD response and static force magnitudes. Moreover, despite the presence of dynamic response elements, offline force classification performance remained relatively stable throughout the go phase ( Figures 6, 6-1), suggesting that the tonic elements could allow for adequate real-time force decoding using linear techniques alone.…”
Section: Decoding Motor Parameters With Dynamic Neural Representationsupporting
confidence: 81%
See 4 more Smart Citations
“…However, the presence of tonic elements agrees with intracortical studies (Smith et al, 1975;Wannier et al, 1991), which demonstrated both tonic and dynamic neural responses to executed forces; and fMRI studies (Branco et al, 2019), which demonstrated a monotonic relationship between the BOLD response and static force magnitudes. Moreover, despite the presence of dynamic response elements, offline force classification performance remained relatively stable throughout the go phase ( Figures 6, 6-1), suggesting that the tonic elements could allow for adequate real-time force decoding using linear techniques alone.…”
Section: Decoding Motor Parameters With Dynamic Neural Representationsupporting
confidence: 81%
“…Second, force-tuned neurons in motor cortex respond more to the direction of applied force rather its magnitude (Kalaska and Hyde, 1985;Kalaska et al, 1989;Taira et al, 1996). Finally, intracortical non-human primate studies (Georgopoulos et al, 1983;Georgopoulos et al, 1992) and fMRI studies in humans (Branco et al, 2019) suggest that motor cortical neurons respond more to the dynamics of force than to static force tasks. The present work, which recorded from rostral motor cortex and studied the representation of static, non-directional forces, may therefore have detected weaker force-related representation than would have been possible from more caudally-placed recording arrays during a dynamic, functional force task.…”
Section: Go-phase Grasp Representationmentioning
confidence: 99%
See 3 more Smart Citations